2012
DOI: 10.1080/00207233.2012.674780
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-assisted low pressure UV photodegradation of atrazine in aqueous solution

Abstract: Aqueous solutions of atrazine (ATZ, 2-chloro-4-ethylamino-6-isopropylamino-1, 3, 5-triazine) were photolysed (λ = 254 nm) by low pressure UV/H 2 O 2 process (LP/UV/H 2 O 2 ) under a variety of parameters including hydrogen peroxide, the initial concentration of ATZ, pH, and humic acid. The results show that the most favourable reaction condition appears to be a moderate concentration of H 2 O 2 from 100 mg/L to 120 mg/L. The presence of humic acid in the solution has a negative impact on the LP/UV/H 2 O 2 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Chen et al reported that O 2 • − occurs in TC aqueous solution under simulated sunlight illumination [ 19 ]. The O 2 • − can disproportionally generate H 2 O 2 , which can be decomposed to •OH under light illumination [ 42 ]. Liu et al investigated the •OH occurring in oxytetracycline (OTC) aqueous solution under UV light illumination and found that the oxygen molecule could accept an electron to form O 2 • − , be decomposed to yield H 2 O 2 [ 43 ] and, in turn, yield oxygen-dependent •OH under light illumination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al reported that O 2 • − occurs in TC aqueous solution under simulated sunlight illumination [ 19 ]. The O 2 • − can disproportionally generate H 2 O 2 , which can be decomposed to •OH under light illumination [ 42 ]. Liu et al investigated the •OH occurring in oxytetracycline (OTC) aqueous solution under UV light illumination and found that the oxygen molecule could accept an electron to form O 2 • − , be decomposed to yield H 2 O 2 [ 43 ] and, in turn, yield oxygen-dependent •OH under light illumination.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxylation byproducts and water loss from the OTC photoreaction could be generated in OTC aqueous solution under UV light illumination [ 43 ]. The production of OH radicals from the photolysis of the –O–O– peroxidic bond via H 2 O 2 under UV illumination can attack organic molecules [ 42 ]. Niu et al reported that the TC photoreaction can react with O 2 • − directly and undergo O 2 • − -mediated self-sensitized photolysis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, advanced oxidation processes (AOPs) have become important technologies for water treatment [1,2] and have been reported for the effective destruction of refractory pollution [2][3][4]. In AOPs, the principal oxidising species are highly active hydroxyl radicals ( Å OH), which have been proposed as an oxidant [5].…”
Section: Introductionmentioning
confidence: 99%